2016
DOI: 10.15376/biores.12.1.514-532
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanism of Self-Bonding of Bamboo Binderless Boards: Investigating the Structural Changes of Lignin Macromolecule during the Molding Pressing Process

Abstract: Binderless boards were produced from bamboo particles through a molding pressing process. The boards were investigated for the chemical and structural changes of lignin and their mechanical strengths to evaluate the mechanism of self-bonding. The structural transformations of milled wood lignin (MWL) obtained from raw bamboo and molding pressed bamboo boards were investigated by Fourier transform infrared (FT-IR), gel permeation chromatography (GPC), quantitative 13 C-NMR spectra, two-dimensional heteronuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Heating temperature seems to be the most influential parameter of lignin changes, subsequently affecting the properties of binderless board. A similar conclusion has been reported by Hashim et al [20], Salvadó et al [21], and Wang et al [22].…”
Section: Introductionsupporting
confidence: 89%
“…Heating temperature seems to be the most influential parameter of lignin changes, subsequently affecting the properties of binderless board. A similar conclusion has been reported by Hashim et al [20], Salvadó et al [21], and Wang et al [22].…”
Section: Introductionsupporting
confidence: 89%
“…In fiberboard production, during thermomechanical pulping, woodchips are converted to lignin-covered fibers by shearing wood fibers along the lignin-rich middle lamellae (Felby et al 1997;Kharazipour et al 1998). Goring (1971), Yelle (2001), van Dam et al (2004, Bouajila et al (2005), Okuda et al (2006a, b), Halvarsson et al (2009), Wang et al (2017) and Laine et al (2019) suggested that lignin has an important role in the production of binderless boards due to the softening of lignin at elevated temperatures and under pressure, fibers with lignin-rich surfaces fuse together as the softened lignin molecules flow from one fiber surface to another one, and possibly form covalent bonds too. If the water content of the raw material is above or near the saturation point, the T g of the cell wall polymers is relatively low.…”
Section: Binderless Boardsmentioning
confidence: 99%
“…Acid-insoluble lignin content increased by about 5% for both tissues. Although the pressing temperature at 150°C and a moisture content of 2% used to make the studied boards may have allowed lignin plasticization to occur (Bouajila et al, 2006;Poletto, 2017;Tejado, Peña, Labidi, Echeverria, & Mondragon, 2007), this temperature is lower than the temperature reported for lignin degradation which starts at around 180°C (Lamaming et al, 2013;Özgenç, Durmaz, Boyaci, & Eksi-Kocak, 2017;Wang et al, 2016). And considering that although during the hot-pressing process higher temperatures than the hot plates are likely to occur due to high pressures and vapor generation, the venting step after the first 30 s of pressing to allow the discharge of initial vapor may have prevented an excessive temperature increase in the mat core (Myron, 1977).…”
Section: Thermal Properties Of Boards Made At 150°c With One and Two Hot-pressing Cyclesmentioning
confidence: 84%
“…Studies have shown that during the dry-forming process of binderless boards the initial moisture content is an important factor and its internal distribution and effects depend highly on the material used (Hidayat, Keijsers, Prijanto, Van Dam, & Heeres, 2014;Uitterhaegen et al, 2017). Although some initial moisture content may promote the glass transition of biopolymers such as lignin during the hot-pressing, which could undergo plasticization and enhance the particles' self-bonding at lower temperatures (Bouajila et al, 2005;Rouilly, Orliac, Silvestre, & Rigal, 2001;Wang et al, 2016), the rapid formation of vapor during the hot-pressing process may also promote the formation of micro-fissures and blisters inside the boards that affect their mechanical properties (Evon, Vinet, Labonne, & Rigal, 2015;Uitterhaegen et al, 2017). With these considerations previous tests were conducted to define the optimal initial moisture content.…”
Section: Previous Tests Conducted To Define the Appropriate Boards' Production Methodologymentioning
confidence: 99%
See 1 more Smart Citation